Uma lupa sobre a política agroalimentar do município de Anchieta sob a perspectiva da inovação social - Julie Rossato Fagundes; Silvio Antonio Ferraz Cario; Alexandre Marino Costa (Confins)
The need to transition current food systems has highlighted the urgency of placing Food and Nutritional Security (FNS) at the center of the food policy of States and governments, imposing a commitment to health and social change, through public policy that can provide answers effectively meet these demands. In this context, the proposal of social innovation opens spaces for new theoretical approaches and practices of governance, like what has been developed in Anchieta, in the western region of Santa Catarina, Brazil. Municipality with an intense agricultural vocation and articulated for the conservation of its agrobiodiversity, it has been a protagonist in the construction of effective policies to support the production, supply and consumption of food, with strong mobilization and social participation. Given this context, this work is characterized as a Case Study, and aimed to identify elements of social innovation in the food agenda of this municipality, based on the theoretical framework proposed by Neumeier (2012;2017). Through analysis of the empirical trajectory and content analysis of the interviews carried out, it is possible to infer that the actions developed reflect elements of approximation with the perspective of social innovation, by exposing the social practice of the actors involved and the appreciation of collective well-being. The Anchietense experience can serve as a reference to other municipalities, since social innovation is triggered by an initial internal or external impulse, but the consolidation dynamics of this process mainly involves the alignment of interests of the participating actors, constituting a process evolutionary process of mutual learning and governance.